MULTIVARIATE ANALYSIS FOR YIELD AND ITS COMPONENT TRAITS IN MAIZE (ZEA MAYS L.) UNDER HIGH AND LOW N LEVELS - KUMAR, NARENDRA; V. N. JOSHI; M. C. DAGLA (The Bioscan, 2013)
A study was carried out using 256 full sib progenies of a large random mating population of maize composite Mahidhawal under two environments of fertility viz., (i) high N (E1) and (ii) low N (E2) to identify efficient full sibs under variable N levels. The highest per cent increase in mean values under high N was observed for grain yield plant-1 (9.21%) followed by ASI (6.51%) and stover yield plant-1 (6.22%). This suggested high N level had more effect on expression of these traits. Principal component analysis on 11 traits, seven principal components had eigen values more than one and accounted for 75.32% of the total variation. Nitrogen efficiency index with N responsiveness at high N showed that 70 and 112 full sibs respectively, were the best full sibs for N-deficient soils of this region. Presence of significant and positive phenotypic correlation was observed for grain yield plant-1 with ear length, ear girth, 100-grain weight, number of cobs plant-1, stover yield plant-1 and harvest index under both N levels except kernel row ear-1 under low N level. The magnitude of phenotypic correlation of grain yield with other traits was numerically higher at low N level than high N level.